Anthropogenic nutrient loads and season variability drive high atmospheric N2O fluxes in a fragmented mangrove system - N. Regina Hershey (Nature Portfolio, 2021)
Abstract Fragmented mangroves are generally ignored in N2O flux studies. Here we report observations over the course of a year from the Mangalavanam coastal wetland in Southern India. The wetland is a fragmented mangrove stand close to a large urban centre with high anthropogenic nitrogen inputs. The study found the wetland was a net source of N2O to the atmosphere with fluxes ranging between 17.5 to 117.9 µmol m−2 day−1 which equated to high N2O saturations of between 697 and 1794%. The average dissolved inorganic nitrogen inputs (80.1 ± 18.1 µmol L−1) and N2O emissions (59.2 ± 30.0 µmol m−2 day−1) were highest during the monsoon season when the rainfall and associated river water inputs and terrestrial runoff were highest. The variation in N2O dynamics was shown to be driven by the changes in rainfall, water column depth, salinity, dissolved oxygen, carbon, and substrate nitrogen. The study suggests that fragmented/minor mangrove ecosystems subject to high human nutrient inputs may be a significant component of the global N2O budget.